Statolith Microstructure Estimates of the Age, Growth, and Population Structure of Purpleback Flying Squid (Sthenoteuthis oualaniensis) in the Waters of the Xisha Islands of the South China Sea - Huajie Lu; Ziyue Chen; Kai Liu; Yuzhe Ou; Maolin Zhao; Tianzi Sun (Fishes, 2022)
In this study, we aimed to estimate the age, growth, and population structure to explore the life history of purpleback flying squid (Sthenoteuthis oualaniensis) by statolith microstructure in the waters of the Xisha Islands of the South China Sea. The purpleback squid, S. oualaniensis, has been the most important economic cephalopod resource of the South China Sea; however, little is known about its life history, especially its age and population structure. The age and growth pattern have been explored via the statolith microstructure of this species of squid, specimens of which were caught randomly between January and March and between May and August of 2018, 2019, and 2020 in the waters surrounding the Xisha Islands of the South China Sea. The results indicated that the range of the mantle length (ML) was 63–229 mm for females and 59–184 for males, and the body weight (BW) ranged from 13 to 435 g for females and from 7 to 152 g for males; the ages were estimated as being between 81 and 298 days for females and between 67 and 286 days for males, respectively. The hatching date extended from January to December, with a peak between November and March of the following year, suggesting the presence of one spawning group (winter–spring group). Significant differences existed between the ML growth and the BW growth. The relationships between ML and age were best described by the linear function for females and the power function for males; the relationship between BW and age were best described by the exponential function for females and the power function for males, based on our AIC models, respectively. S. oualaniensis is a fast-growing squid; the growth rate is the fastest during the young life stage, and it decreases after the subadult stage (120–150 days). After the first spawning behavior, the inflection point of the growth was recognized at the age of 180–210 days (6–7 months). This study provided basic, favorable information for the fishery biology, ecology, and resource management of purpleback flying squid (S. oualaniensis) of the South China Sea.